Assessing the impact of the economic crises in 1997 and 2008 on suicides in Hong Kong, Taiwan and South Korea using a strata-bootstrap algorithm - Soleymani, Mehdi (Journal of applied statistics, 2020)
© 2019 Informa UK Limited, trading as Taylor & Francis Group.